Artificial intelligence and the productive accountant - Sikow, Julius (My University, 2025)
The effects of digitalisation on management accounting and business controllers have been significant. Digitalisation has led to the automation of tasks and improved analytical capabilities, allowing business controllers to establish themselves as business partners. Recently, the academic discussion surrounding the role of management accounting has shifted from the ideal of the business partner to normative ideals such as productivity, with emphasis on efficiency and output. Organisations often utilise technology, such as artificial intelligence, to boost productivity, which is frequently accompanied by a change in how performance is assessed. The productivity agenda can redirect the focus of a business controller’s work from the ideals of a business partner to more measurable productivity outcomes. The objective of this thesis was to examine how artificial intelligence affects the role of a business controller. Specifically, the aim was to examine how artificial intelligence influences the productive management accountant role of a business controller. A productive management accountant refers to a business controller whose work is guided and evaluated by normative ideals associated with productivity. This study is qualitative in nature, and its empirical data were collected through semi-structured interviews with management accounting professionals from four organisations in the Finnish energy sector. The data was then analysed using content analysis. The results indicate that artificial intelligence has had only a limited impact on the role of a business controller. Its use in management accounting tasks is non-existent, but the results show that artificial intelligence is widely used in support of routine tasks. Its impact is perceived as positive because it simplifies and eases routine tasks. The results indicate that artificial intelligence enables business controllers to seek their wanted selves, by distancing themselves from routine tasks associated with the un-wanted selves. Overall, the findings show that the evaluation of business controllers remains grounded in the ideals of the business partner role. The findings indicate that artificial intelligence is expected to substantially impact management accounting through the automation of routine tasks and by enhancing analytical capabilities. These developments are expected to further align the business controller’s role as a strategic business partner.

Digitalisaatio on vaikuttanut merkittävästi johdon laskentatoimeen ja business controllerin työhön. Digitalisaatio on johtanut tehtävien automatisointiin sekä parantanut business controllerien analyyttisiä valmiuksia, minkä ansiosta business controllerit ovat voineet asemoida itsensä liiketoimintaa tukevina ammattilaisina. Viime aikoina akateemisen tutkimuksen fokus johdon laskentatoimen tutkimuksessa on siirtynyt liiketoiminnan tukemisesta muihin ihanteisiin, kuten tuottavuuteen, jossa painottuu tehokkuus ja tulokset. Organisaatiot ottavat usein käyttöön teknologioita, kuten tekoälyn parantaakseen tuottavuutta. Tuottavuusprojekteihin kuuluu myös usein suorituskyvyn mittauksen painotuksen muuttaminen tuottavuuden suuntaan. Business controllerin työhön tuottavuusagenda voi vaikuttaa muuttamalla työn kohdistumisella tuottavuutta korostaviin, mitattavissa oleviin tuloksiin liiketoimintakumppaniin liitetyistä ihanteista poiketen. Tämän tutkielman tavoitteena oli tutkia kuinka tekoäly vaikuttaa business controllerin rooliin. Tarkempana tutkimusasetelmana oli tutkia kuinka tekoäly vaikuttaa tuottavaksi johdon laskentatoimen ammattilaiseksi kutsuttuun business controllerin rooliin. Tällä roolilla tarkoitetaan business controlleria, jonka työtä ja arviointia ohjaa tuottavuus. Tämä tutkimus on laadullinen tutkimus, jonka empiirinen tukimusainesto koostuu puolistrukturoidusta haastattelusta. Haastateltavina toimivat neljä johdon laskentatoimen ammattilaista, jotka työskentelevät Suomessa energia-alalla eri organisaatioissa. Empiirinen aineisto analysoitiin käyttäen sisällönanalyysiä. Tulokset osoittavat, että tekoälyllä on ollut vain rajallinen vaikutus business controllerin rooliin. Business controllerit eivät vielä ole ottanut sitä käyttöön johdon laskentatoimen tehtävissä, mutta business controllerit käyttävät sitä rutiinitehtävien tukena, missä sen vaikutus on nähty positiivisena. Tulokset osoittavat, että tekoäly auttaa business controllereita toteuttaa haluamaansa itsekuvaa, koska sen avulla pystyy ottamaan etäisyyttä rutiinitehtävistä, jotka liittyvät ei-toivottuun itsekuvaan. Empiiriset tulokset osoittavat, että business controllereiden arviointi perustuu edelleen liiketoimintakumppanin roolin ihanteisiin. Tulokset viittaavat siihen, että tekoälyn odotetaan vaikuttavan merkittävästi liiketoiminnan laskentatoimeen automatisoimalla rutiinitehtäviä ja parantamalla analyyttisiä valmiuksia. Näiden kehityssuuntausten odotetaan vahvistavan business controllereiden roolia strategisena liiketoimintakumppanina.
Keywords: Management accounting, business controller, productive management accountant, artificial intelligence, johdon laskentatoimi, business controller, tuottava johdon laskentatoimen ammattilainen, tekoäly